ANALISIS MOTIVASI BELAJAR MATEMATIKA SISWA SMA KETIKA KEMBALI BELAJAR TATAP MUKA - Sulis Regita Cahyani; Attin Warmi (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
AbstractThis study aims to find the motivation to learn mathematics at high school (SMA) students when they return to face-to-face learning at school. This research is a qualitative research with descriptive analysis method. The population in this study were students of class XI MIPA 3, in one of the public schools in the Karawang district for the academic year 2022/2023. The sample used in this study were 36 students. The data collection technique in this study used a high school student learning motivation questionnaire when returning to face-to-face learning which contained 23 statements with 12 positive statements and 11 negative statements and conducted interviews with students. The results of data analysis in this study were at a percentage of 74% which showed that students had a good level of motivation to learn mathematics when they returned to face-to-face learning at school.Keywords: Learning Motivation, Online Learning, Face-To-Face Learning